Trigonometric Summation!

Calculus Level 3

n = 1 arccot ( n 2 + n + 1 ) \sum_{n = 1}^{\infty} \text{arccot }(n^{2} + n + 1)

Calculate the sum above to 3 decimal places.

Courtesy: Stewart Calculus Early Transcendentals Sixth Edition


The answer is 0.78539816339.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Torus Wheel
Jun 25, 2018

Solution :

n 2 + n + 1 = n ( n + 1 ) + 1 n^{2} + n + 1 = n \cdot (n + 1) + 1

Therefore:

Using the identity : a r c t a n ( x ) a r c t a n ( y ) = a r c t a n ( x y 1 + x y ) arctan(x) - arctan(y) = arctan(\frac{x - y}{1 + x \cdot y}) ;

Let x = n + 1 x = n + 1 and y = n y = n .

Then,

a r c t a n ( n + 1 ) a r c t a n ( n ) = a r c t a n ( ( n + 1 ) n n ( n + 1 ) + 1 ) = a r c c o t ( n ( n + 1 ) + 1 ( n + 1 ) n ) arctan(n + 1) - arctan(n) = arctan(\frac{(n + 1) - n}{n \cdot (n + 1) + 1}) = arccot(\frac{n \cdot (n + 1) + 1}{(n + 1) - n}) [ a r c t a n ( x ) = a r c c o t ( 1 x ) ] [arctan(x) = arccot(\frac{1}{x})]

Thus,

a r c c o t ( n 2 + n + 1 ) = a r c t a n ( n + 1 ) a r c t a n ( n ) arccot(n^{2} + n + 1) = arctan(n + 1) - arctan(n)

So,

n = 1 a r c c o t ( n 2 + n + 1 ) = n = 1 ( a r c t a n ( n + 1 ) a r c t a n ( n ) ) \sum_{n = 1}^{∞} arccot(n^{2} + n + 1) = \sum_{n = 1}^{∞} (arctan(n + 1) - arctan(n)) ,

The sum is now equal to : a r c t a n ( 2 ) a r c t a n ( 1 ) + a r c t a n ( 3 ) a r c t a n ( 2 ) + a r c t a n ( 4 ) a r c t a n ( 3 ) + arctan(2) - arctan(1) + arctan(3) - arctan(2) + arctan(4) - arctan(3) + .......

This sum telescopes to : ( lim n a r c t a n ( n ) ) a r c t a n ( 1 ) (\lim_{n\to ∞} arctan(n)) - arctan(1) , which is equal to π 2 π 4 \frac{π}{2} - \frac{π}{4} which is equal to π 4 \frac{π}{4} .

Chew-Seong Cheong
Jun 25, 2018

Solution similar to @Torus Wheel 's

S = n = 1 arccot ( n 2 + n + 1 ) = n = 1 arctan ( 1 n 2 + n + 1 ) = n = 1 arctan ( ( n + 1 ) n 1 + ( n + 1 ) n ) = n = 1 ( arctan ( n + 1 ) arctan ( n ) ) = lim n arctan ( n + 1 ) arctan ( 1 ) = π 2 π 4 = π 4 0.785 \begin{aligned} S & = \sum_{n=1}^\infty \text{arccot }(n^2+n+1) \\ & = \sum_{n=1}^\infty \arctan \left(\frac 1{n^2+n+1}\right) \\ & = \sum_{n=1}^\infty \arctan \left(\frac {(n+1)-n}{1+(n+1)n}\right) \\ & = \sum_{n=1}^\infty \left(\arctan (n+1) - \arctan (n)\right) \\ & = \lim_{n \to \infty} \arctan (n+1) - \arctan (1) \\ & = \frac \pi 2 - \frac \pi 4 = \frac \pi 4 \approx \boxed{0.785} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...